2020
DOI: 10.24203/ajafs.v8i4.6262
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Small Scale Farmers’ Low Levels of Adoption to Crop Insurance as an Adaptation Strategy to Climate Variability in Nyandarua County of Kenya

Abstract: Kenya is one of the many countries in Sub Saharan Africa affected by climate variability and its related hazards due to changes in temperature and variations in rainfall in most parts of the country. The present study has been undertaken to assess the adaptation strategies applied by the small scale farmers in response to climate variability in Nyandarua County. The study has been conducted in central region of Kenya which is relatively humid and good for agricultural production. A total sample size of 300 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As noted by Opanda ( 2021), specialised knowledge is often required for greenhouse technology; a lack of extension support thus is expected to present challenges where extension services are lacking or inadequate. Muriithi et al (2021) observed that GHT requires adequate expertise, indicating a need for technical information to initiate and sustain the GHT system. The lack of scientific information on greenhouse farming was identified as a major challenge among smallholders (Wayua et al, 2020).…”
Section: Poor Access To Information and Extension Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted by Opanda ( 2021), specialised knowledge is often required for greenhouse technology; a lack of extension support thus is expected to present challenges where extension services are lacking or inadequate. Muriithi et al (2021) observed that GHT requires adequate expertise, indicating a need for technical information to initiate and sustain the GHT system. The lack of scientific information on greenhouse farming was identified as a major challenge among smallholders (Wayua et al, 2020).…”
Section: Poor Access To Information and Extension Servicesmentioning
confidence: 99%
“…The lack of relevant information was ranked the fourth most important challenge in their study. Muriithi et al (2021) similarly pointed out that lack of information was a major constraint in the utilisation of greenhouse technology as a measure to mitigate climate variability. Elsewhere in other crops, crop productivity in coffee has been linked to technical information inputs (Cheruiyot, 2022); emphasising the significance of the information inputs on the overall farm productivity.…”
Section: Poor Access To Information and Extension Servicesmentioning
confidence: 99%
See 1 more Smart Citation